Care ethics to develop computing and engineering education for sustainability - Peters, Anne-Kathrin; Bengtsson, Stefan; Cajander, Asa; Daniels, Mats; Grande, Virginia; Lonngren, Johanna; Salminen-Karlsson, Minna (2020 IEEE Frontiers in Education Conference (FIE), 2020)
The aim of this special session is to connect researchers interested in computing and engineering education for sustainability. We will explore the use of care and care ethics as a theoretical perspective to develop sustainability education. Theoretical discussions in environmental and sustainability education (ESE) research and feminist research will be introduced to develop an understanding of care for education. Those theories will be illustrated and motivated based on concrete examples in computing and computing education. The participants get to choose among four different topics of discussion in the session, 1) the role of education to prepare for care, 2) theoretical discussions of care as a concept to develop education and education research, 3) pedagogical methods to foster care, 4) care and responsibility in the curriculum. The outcome of this session is two-fold: The participants will gain new ways of conceiving education for human and planetary well-being and they will get to know researchers and educational developers with an interest in and experiences with sustainability education.